Effects of ambient temperature and humidity on droplet lifetime – A perspective of exhalation sneeze droplets with COVID-19 virus transmission - Chen, Lea-Der (Int J Hyg Environ Health, 2020)
A one-dimensional droplet evaporation model is used to estimate the droplet lifetime from evaporation in air. The mathematical model invokes assumptions of spherical symmetry, ideal gas mixture, binary diffusion, no re-condensation on droplet surface, and constant properties. Four initial droplet diameters (0.001, 0.01, 0.1, and 1 mm), two ambient temperatures (20 and 30 (o)C) and a range of ambient relative humidity are considered. For the conditions studied, the results show that the ambient relative humidity plays an important role in the droplet lifetime calculation. Increasing the ambient temperature does not necessarily decrease the droplet lifetime; it occurs only when the ambient relative humidity is set below 37%. When the ambient relative humidity is higher than 37%, the higher ambient temperature (30 (o)C) results in a longer droplet lifetime for the same initial droplet diameter considered. The results also suggest that there may exist a critical ambient relative humidity; beyond which, the droplet lifetime will increase exponentially. For ambient temperature at 30 (o)C, the critical ambient relative humidity is around 55.7%. It must be mentioned that the results of this study do not imply that the COVID-19 virus will be deactivated at the end of the droplet lifetime. The study simply shows the potential effects resulting from the ambient temperature and ambient relative humidity on virus carrying drops.